Metro TV’s Editorial Strategy to Controversial Sources: The Case Study on Special Report TV Program - Aristia Ningrum, Dian; Briandana, Rizki; Mulyana, Ahmad (Jurusan Ilmu Komunikasi UTM, 2024)
One strategy to pique viewers' interest is to display contentious topics, cases, and sources. Metro TV successfully achieved this with their Special Report,